2012
DOI: 10.1111/j.1743-6109.2012.02954.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Penile Erections: The Role of RigiScan in the Diagnosis of Vascular Erectile Dysfunction

Abstract: Introduction To determine the etiology of cases with organic erectile dysfunction (ED), invasive techniques are needed that can induce patient anxiety and disturb test results. Aim To find any special patterns of nocturnal penile tumescence and rigidity (NPTR) records in cases of vasculogenic impotence that can differentiate cases of arterial and venous origin without resorting to the more invasive diagnostic tests. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
1
24
0
3
Order By: Relevance
“…The IIEF lacks information about the aetiology of sexual disorders (Rosen et al ., ), and the IIEF cannot differentiate between organic and functional ED. Besides, in the evaluation of human erectile function, nocturnal penile tumescence (NPT) monitoring is one of the most reliable methods to diagnose ED and to differentiate psychogenic from organic ED (Elhanbly & Elkholy, ). However, there have been no relevant studies that assessing erectile function in patients with CP/CPPS using NPT monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The IIEF lacks information about the aetiology of sexual disorders (Rosen et al ., ), and the IIEF cannot differentiate between organic and functional ED. Besides, in the evaluation of human erectile function, nocturnal penile tumescence (NPT) monitoring is one of the most reliable methods to diagnose ED and to differentiate psychogenic from organic ED (Elhanbly & Elkholy, ). However, there have been no relevant studies that assessing erectile function in patients with CP/CPPS using NPT monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Kassouf & Carrier () concluded that the use of only IIEF cannot be a tool to diagnose or compare specific vascular causes of ED. Therefore, the NPT measurement should be considered an essential diagnostic tool for ED diagnosis with a high accuracy in men with suspected ED (Tokatli et al ., ; Elhanbly & Elkholy, ). An increase of ≥15 min in the penile tumescence over 200% at the tip was interpreted as a normal and sufficient erection in all men regardless of age, when the Neva ® device was applied for NPT measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Rigiscan test is useful in the diagnosis of erectile dysfunction (ED) to distinguish organic and psychogenic ED (Marshall, Morales, & Surridge, ). A normal NPT is defined as more than three erectile episodes with a duration over 10 min as well as tip and base rigidity ≥70%, and tip tumescence ≥2 cm and base tumescence ≥ 3 cm (Elhanbly & Elkholy, ). These diagnostic criteria have been a focus of debate and have stressed the diagnostic value of erectile events per night and the data on rigidity and tumescence, while other parameters, including RAU tip, TAU tip, RAU base and TAU base, are less evaluated, which has been implicated to have a role in ED diagnoses (Elhanbly, Elkholy, Elbayomy, Elsaid, & Abdel‐gaber, ).…”
Section: Discussionmentioning
confidence: 99%